A Flexible Country in the Making: Reaction and strategy of the trade union movement to flexibilization in the Netherlands in the 1980s - Kösters, Rosa; van Diepen, Loran; van Dijk, Moira; van Rossum, Matthias (TSEG - The Low Countries Journal of Social and Economic History, 2022)
Internationally, the 1980s marked a shift in economic policy. In the Netherlands, the supposedly moderate neoliberal turn and the first round of flexibilization characterized the decade. Nowadays, labour market flexibility is exceptionally high in the Netherlands compared to neighbouring countries. This article examines how the trade union movement in the 1980s responded to increasing flexibilization, which strategy was used, and how this contributed to early Dutch flexibilization. In contrast to literature reflecting an institutional perspective, the trade union movement is analysed in this article from a social-historical perspective and as a social movement. As a result, it is argued that the effects of rising flexibilization were noted very early on within the trade unions. Be that as it may, both the priorities that followed from the agreements with employer organizations and the internal dynamics were decisive for the trade union movement’s relatively late and unassertive responses to the flexibilization of labour in the 1980s.